2014
DOI: 10.3390/pharmacy2010124
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Survey to Assess the Acceptability of an Innovative Contraception Practice among Rural Pharmacists

Abstract: Improved access to effective contraceptive methods is needed in Canada, particularly in rural areas, where unintended pregnancy rates are high and specific sexual health services may be further away. A rural pharmacist may be the most accessible health care professional. Pharmacy practice increasingly incorporates cognitive services. In Canada many provinces allow pharmacists to independently prescribe for some indications, but not for hormonal contraception. To assess the acceptability for the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…Community pharmacies have potential for expansion of SRH services as revealed in this study. This advantage can be exploited when we consider the fact that studies have shown that community pharmacies are well suited for expanding access to SRH services due to their extensive geographical spread among the populace and their extended opening hours [9,18]. However, this study identified inherent weaknesses in the structures and proces involve in the provision of SRH.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Community pharmacies have potential for expansion of SRH services as revealed in this study. This advantage can be exploited when we consider the fact that studies have shown that community pharmacies are well suited for expanding access to SRH services due to their extensive geographical spread among the populace and their extended opening hours [9,18]. However, this study identified inherent weaknesses in the structures and proces involve in the provision of SRH.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, pharmacies are providing expanded access to family planning especially for unmarried and younger women [6,7]. In developed countries like the United States of America and Canada, many contraceptive products including the hormonal agent levonorgestrel are approved for OTC emergency dispensing, requiring a pharmacist's prescription for insurance reimbursements [8,9]. Similarly, in the United Kingdom community pharmacists evaluate clients and supervise the sale of emergency contraceptive products [10].…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire and the interview script both addressed all conceptual constructs for successful integration of an innovation into practice, as framed within Roger's theory of Diffusion of Innovations [21,22]. We have described the development, review, iterative pilot testing and validation of the survey [20]. Ethics approval was obtained from the University of BC, Children's and Women's Research Ethics Board (H12-01569).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the conceptual frameworks above and previous work [34,35], in October 2015, 4 of our clinicianresearchers who are experts in abortion care (group I: RR, WVN, SD, EG) created a survey instrument with 47 baseline questions and 21 follow-up questions. The questions were developed to assess facilitators and barriers to the adoption of mifepristone into practice as well as the impact of mandatory training on the practice of mifepristone medical abortion.…”
Section: Phase 1: Development Of Preliminary Survey Itemsmentioning
confidence: 99%
“…The Légaré instrument questions applied to a range of content areas; therefore, very few wording changes were required (see Table 3). Appropriate questions stemmed from 3 previously developed and fielded instruments developed by CART for the diffusion of contraception practice innovations [34,35,46] with minor modifications (e.g., "mifepristone" replacing "contraceptive" where appropriate).…”
Section: Development Of Preliminary Survey Items (Phase 1)mentioning
confidence: 99%